The Carpathians: Integrating Nature and Society Towards Sustainability - Kozak, Jacek.; Ostapowicz, Katarzyna.; Bytnerowicz, Andrzej.; Wy|ga, BartBomiej. (Environmental Science and Engineering, Environmental Engineering,, 2013)
The Carpathians are a distinct mountain chain in the core of Central and Eastern Europe holding valuable biological resources and a rich cultural heritage. The last twenty years have witnessed an increasing awareness of the Carpathians<U+0019> value for European society and strengthened research cooperation in the region, especially after the enlargement of the European Union in 2004 and 2007. This book presents a wide range of problems related to sustainable development in the Carpathian region that were discussed during the 1st Forum Carpaticum held in 2010 in Krakw̤, Poland. The four sections of the book deal with various issues related to the abiotic environment, forests and biodiversity, human activities, and research methods allowing a better understanding of the past, present and future of the Carpathians.